2014
DOI: 10.1093/occmed/kqu017
|View full text |Cite
|
Sign up to set email alerts
|

Fatal accidents and injuries among merchant seafarers worldwide

Abstract: The expansion of the British merchant fleet in recent years does not appear to have had a major impact on fatal accidents. Further preventive measures should target fatalities during mooring and towing operations. Internationally, most shipping fleets have over time experienced large decreases in fatal accident rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 10 publications
4
65
0
3
Order By: Relevance
“…By contrast studies investigating seafaring risks in earlier time periods found it to be more hazardous, have a higher mortality rate, and to have had a consistently higher suicide rate than other occupations [2][3][4][5][6][7], yet many of these studies also reported a declining rate of seafarer suicide between the 1960s to the early 2000s. A more revealing picture emerges from looking at these issues within the population of seafarers i.e.…”
Section: General Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast studies investigating seafaring risks in earlier time periods found it to be more hazardous, have a higher mortality rate, and to have had a consistently higher suicide rate than other occupations [2][3][4][5][6][7], yet many of these studies also reported a declining rate of seafarer suicide between the 1960s to the early 2000s. A more revealing picture emerges from looking at these issues within the population of seafarers i.e.…”
Section: General Findingsmentioning
confidence: 99%
“…They often spend months at sea with little or no contact with their life ashore, while working and living in limited spaces where there may be substantial amounts of noise, heat and vibration as well as the motion of the ship [1]. Distance from home and the working and living environment have usually been assumed to contribute to the high suicide rate of seafarers in the past [2][3][4][5][6][7]. The question remains, however, if this is still relevant today.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its influence on health, obesity might be a safety issue for occupational area especially on board at sea due to the fact that it may be difficult for overweight persons to carry out safety tasks in emergency situations, such as escaping from ships and getting on a lifeboat [8]. In this respect, the seafarers should be fit so as to overcome risky situations because fatal accidents and injury rates in maritime industry are higher than in other industries such as construction industry and manufacturing industry [9]. But this situation does not seem very possible because seafarers usually spend a long time on board [10] where their movement areas are limited and the convenience provided by technological devices on board have reduced the demand for muscle power, so they tend to put on weight.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the Alaskan, Icelandic, Norwegian, Polish (trawler) and United States fishing fleets have reported large or moderate reductions over time in fatal accident rates while studies of Danish, British and Polish (small-scale) fishing have reported little or no improvement. This contrasts with trends in fatal accidents in merchant shipping which have usually fallen sharply over time [10]. There have been few reports on long term trends in fatal accidents in fishing industries dating back over the twentieth century and also few reports on mortality rates from disease, suicide and homicide in fishing industries.…”
Section: Introductionmentioning
confidence: 92%